2013
DOI: 10.4321/s0465-546x2013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Violencia contra trabajadores sanitarios en un hospital de Andalucía: ¿Por qué hay agresiones no registradas?

Abstract: Violencia contra trabajadores sanitarios en un hospital de Andalucía, ¿por qué hay agresiones no registradas?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
1
1
0
3
Order By: Relevance
“…The age group with the highest proportion of recorded attacks was between 46 and 55 years old, a range higher than that described in other Spanish studies (30–43 years) [ 14 – 16 , 18 , 19 ]; but closer to the most affected ages described in international studies: Canada (44 years) [ 17 ], Australia (45–54 years old) [ 20 ] and Germany (55 years old) [ 17 ]. That is, our results support the hypothesis that the profile of the physician attacked is not necessarily a young physician with little experience as other authors have suggested [ 15 , 21 ].…”
Section: Main Textsupporting
confidence: 91%
“…The age group with the highest proportion of recorded attacks was between 46 and 55 years old, a range higher than that described in other Spanish studies (30–43 years) [ 14 – 16 , 18 , 19 ]; but closer to the most affected ages described in international studies: Canada (44 years) [ 17 ], Australia (45–54 years old) [ 20 ] and Germany (55 years old) [ 17 ]. That is, our results support the hypothesis that the profile of the physician attacked is not necessarily a young physician with little experience as other authors have suggested [ 15 , 21 ].…”
Section: Main Textsupporting
confidence: 91%
“…Un elevado porcentaje de entrevistados no ha interpuesto denuncias a nivel legal, ni ha realizado un registro de las agresiones sufridas coincidiendo con otros investigadores 2 , 11 , 21 , 25 .…”
Section: Resultados Y Discusiónunclassified
“…La violencia en el lugar de trabajo, sea física o psicológica, se ha convertido en un problema mundial que atraviesa las fronteras, los contextos de trabajo y los grupos profesionales 1 . En la última década, según el informe de los Centros para la Prevención y Control de Enfermedades las agresiones laborales se han incrementado en un 300% 2 .…”
Section: Introductionunclassified
“…La falta de denuncia es otro problema recurrente, que dificulta, entre otros, las actuaciones requeridas para la calificación y enjuiciamiento de estos episodios violentos 5 . Los programas de formación que inciden en la importancia del registro de cualquier tipo de agresión, podrían ser de ayuda en la concienciación de los trabajadores 19 , ya que hasta el momento tienden a minimizar la importancia de los incidentes e incluso considerarlos parte de la profesión 16,19 .…”
Section: El Fenómenounclassified